EFEKTIFITAS KERJA DALAM MENANGULANGI MASALAH KEMACETAN (SUATU STUDI DI DINAS PERHUBUNGAN KOTA MANADO) - LOSA, CALVIN (Sam Ratulangi University, 2016)
Congestion in Manado city is generally caused by the growing number or the increase of the volume ofvehicles in every year that was not balanced with the capacity of roads, community awareness for the use ofpublic transportation is also still lacking, this is because the public transport in the city of Manado has yetto fully meet the standards, and many are not worth to use. Departing from the above problem, which isthe purpose of this research is to know the effectiveness of work apparatus can affect the problemof congestion in the town of ManadoThis study uses qualitative methods of approach. The object examined relates to the effectiveness of thework in the congestion problem in the city of Manado in the study then the determinationof the informant set as many as 8 people. Data analysis techniques are divided into 3 stages, namely, datacollection, data presentation, data reduction, and withdrawal of the summary.Results of the study prove that transportation management stillconsidered insufficient. Less effective management of transportation greatly affects the traffic congestionproblem, which so much is because the land area for the use of roads especially to streamline the activitiesof the transportation/traffic movement have been very cramped and there is no improvement, so it isnot capable of holding the vehicle so much. For the infrastructure of roads such as the placementof signs and road markings are considered less effective because it still gives rise to various bottlenecks. Theimpact of traffic congestion is very influential towards the traffic activity, some of the impact inflicted veryinfluential on aspects of economic, social, cultural and security.Key Words: Effectiveness Of Public Works, Transport, The Congestion Problem